Efficient online/offline signcryption without key exposure. (1st January 2013) - Yan, Fei; Chen, Xiaofeng; Zhang, Yinghui
An online/offline signcryption scheme provides confidentiality and authentication simultaneously, and it is particularly suitable for the application of resource-constrained systems. In this paper, we present a key-exposure free online/offline signcryption scheme. In contrast, it seems that all the existing online/offline signcryption schemes based on Shamir-Tauman's paradigm suffer from the key exposure problem. In the random oracle model, the proposed scheme is proved to be indistinguishable against adaptive chosen-ciphertext attacks (IND-CCA2) and existentially unforgeable against chosen-message attacks (EUF-CMA). Besides, an improved scheme is proposed, which requires none of the recipient's public information in the offline phase and hence makes practical sense.